First account on feeding and reproductive biology of Aluterus scriptus (Osbeck, 1765) from the southern coast of India - Rajarajan Tamilselvan; Paulraj Jawahar; Natarajan Jayakumar; Rajagopal Santhakumar; Velu Rani; Shanmugam Sundhar; Thirumal Iyyappan; Esakkimuthu Dineshkumar; Soosaiantony Emiema (Journal of Fisheries, 2026)
Aluterus scriptus (Osbeck, 1765) is a reef-associated fish from the Monacanthidae family. The data on its reproductive and feeding biology are currently scarce. Exploring these aspects is crucial for gaining insights that help in developing effective conservation strategies. A total of 900 specimens of A. scriptus were studied from February 2022 to January 2023. The samples were investigated for length-weight relationship, food and feeding habits, sex ratio, length at first maturity, spawning seasonality and fecundity. The observed mean length and weight were 50.2±14.7 cm and 1094±374.4 g, respectively. Growth was negatively allometric, with no significant differences observed between sexes in the length–weight relationship. The mean sex ratio (M:F) of 1:1.53 indicates a female-biased population, with a month-to-month variation in sex ratio. The estimated length at first maturity was 53.33 cm for females and 54.21 cm for males. Reproductive activity is observed throughout the year, with the peak occurring in December.  A strong positive correlation was observed between the fecundity and total length (Pearson’s r = 0.986, p < 0.001). Seasonal variation in stomach fullness suggested fluctuations in feeding intensity. Diet analysis revealed a strong preference for coral, followed by small crustaceans, fish, jellyfish, and squid. These findings provide baseline data for the responsible management of A. scriptus fishery.